Kriminalisasi Nikah Sirri Menurut Rancangan Undang-Undang Hukum Materiil Peradilan Agama Bidang Perkawinan - Efendi, Roni (Universitas Muhammadiyah Sumatera Barat, 2019)
Criminal policies in criminal law can be applied with dual track system approach, the first Penalism approach as part of an ultymum remedium that is reduced from the punishment theory. Then, non-criminal approach prioritize the primum remedium path that puts more emphasis on sanctions. Ultimatum remedium applicable only to tackle crime, it can be implemented with no alternative, but the government seeks a draft Law on Material Law Courts for Marriage which criminalizes behavior previously not lawful even according to religious norms, the act is the not recorded. This rule becomes one of the meanings used to create works that are different from law enforcement, certainty and law enforcement purposes.